Rhythm-based assessment and training for children with attention deficit hyperactivity disorder (ADHD): a feasibility study protocol - Shin, Hye Jin; Lee, Hyun Ju; Kang, Dahyun; Kim, Johanna Inhyang; Jeong, Eunju (Frontiers in Human Neuroscience, 2023)
Background: The timing-related deficits in individuals with attention deficit hyperactivity disorder (ADHD) contribute to the symptom-related difficulties and cognitive impairments.Current assessment and training measurement only target specific aspects of the timing ability, highlighting the need for more advanced tools to address timing deficits in ADHD.The aim of this study is to develop and validate a rhythm-based assessment and training (RAT) program, which intends to provide a comprehensive understanding of and enhancement to the time-related abilities of children with ADHD, thereby demonstrating its clinical efficacy.Methods: We will use randomized crossover trials in this study, with participants being randomly assigned to either start with the RAT and then proceed to cognitive training or start with cognitive training and then proceed to the RAT. Both groups will undergo pre-and postevaluations. The evaluation will be administered immediately before and after the 4-week training period using diagnostic questionnaires, cognitive evaluation tools, and resting electroencephalography (EEG) measurements. Notably, EEG measurements will be conducted concurrently with the RAT evaluations.Discussion: This study develops and evaluates the feasibility and effectiveness of a RAT while using EEG measurements to elucidate the underlying therapeutic mechanism of auditory rhythm at varying levels of complexity. The study will investigate the potential of RAT as a supplementary or alternative approach for managing ADHD. The multifaceted data collected will yield valuable insights to customize training agendas based on individual developmental stages and prognoses.